What Motivates Mobile E-Book Use among Mathematics Postgraduate Students? - Letchumanan, Malathi; Muniandy, Balakrishnan; Mohamad, Mariam; Said Husain, Sharifah Kartini (International Journal of Evaluation and Research in Education (IJERE), 2022)
This paper aims to understand the factors that encourage the use of mobile e-books among mathematics postgraduate students. Eight mathematics postgraduate students from a local public university in Malaysia participated in the study. The participants were from Algebra research group. This study employed qualitative case study approach. Data were collected via interview and non-participant observation. Collected data were analysed by using constant comparative analysis. This study used three theoretical frameworks as its guiding theory, namely Technology Acceptance Model, Pleasure, Arousal and Dominance Theory and Diffusion of Innovation Theory to explore the factors that influence the use of mobile e-book among the participants.Â  Findings showed that utilitarian, cognitive, affective, social norm and content qualities were the main factors influencing the use of mobile e-books among the participants. This study also demonstrated that the participants were interested in using mobile e-book and this may assist academicians and mobile e-book designers in improving and understanding the use of mobile e-book among mathematics postgraduate students. This study could contribute in terms of expanding readersâ€™ understanding on the factors that motivate use of mobile e-book among mathematics postgraduate students for their learning activities.